2017
DOI: 10.5115/acb.2017.50.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Vanillin and 4-hydroxybenzyl alcohol attenuate cognitive impairment and the reduction of cell proliferation and neuroblast differentiation in the dentate gyrus in a mouse model of scopolamine-induced amnesia

Abstract: 4-Hydroxy-3-methoxybenzaldehyde (vanillin) and 4-hydroxybenzyl alcohol (4-HBA) are natural phenolic compounds, which present in many plants and have diverse biological properties. In this study, we examined effects of vanillin and 4-HBA on learning and memory function, cell proliferation, and neuroblast differentiation in the hippocampal dentate gyrus in a mouse model of scopolamine-induced amnesia. Scopolamine (SCO; 1 mg/kg/day, intraperitoneally), vanillin, and 4-HBA (40 mg/kg/day, orally) were administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The improvement in passive avoidance memory was accompanied by the enhancement of cell proliferation in the hippocampal DG, suggesting that an increase in newborn neurons was involved in retention and recall memory (Oh et al, 2006;Yang et al, 2008;Kim and Park, 2017;Takahashi et al, 2017). In the present study, OBX mice showed a significant decrease in cell proliferation in the DG compared to the sham group which is consistent with our previous study (Nakagawasai Takahashi et al, 2017, Takahashi et al, 2018b, while this change was reversed by the SG-ME treatment [ Figure 5B].…”
Section: Discussionsupporting
confidence: 92%
“…The improvement in passive avoidance memory was accompanied by the enhancement of cell proliferation in the hippocampal DG, suggesting that an increase in newborn neurons was involved in retention and recall memory (Oh et al, 2006;Yang et al, 2008;Kim and Park, 2017;Takahashi et al, 2017). In the present study, OBX mice showed a significant decrease in cell proliferation in the DG compared to the sham group which is consistent with our previous study (Nakagawasai Takahashi et al, 2017, Takahashi et al, 2018b, while this change was reversed by the SG-ME treatment [ Figure 5B].…”
Section: Discussionsupporting
confidence: 92%
“…Passive avoidance test was used to measure short-term memory in the treated rats from the different groups in this study. The test was performed according to the modified procedure published by Lee et al [ 26 ] and Kim and Park [ 27 ]. Briefly, the procedure utilized an apparatus that consisted of light and dark compartments lined with white Formica.…”
Section: Methodsmentioning
confidence: 99%
“… 42 45 In addition, vanillin has been shown to attenuate scopolamine-induced cognitive impairment via modulating the DNA-binding protein inhibitor ID-1 and neuronal differentiation. 46 , 47 Ethyl methoxycinnamate reportedly improves cognitive impairment independent of direct acetylcholinesterase and glutamate receptor inhibition in an aluminum-induced memory deficit rat model. 41 Moreover, cinnamaldehyde attenuates cognitive deficits via regulating extracellular signal-regulated kinase signaling in the prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%